Insecticide Resistance Profile of Mosquitoes: A Study of a Residential and Industrial Breeding Sites in Kano Metropolis, Nigeria - Chimaobi J Ononamadu; John T Datit; Abdullahi A Imam (SAGE Publishing, 2020)
Monitoring and understanding the trend and dynamics of insecticide resistance is very key to devising efficient control strategies. This study was carried out to characterize the mosquito population, its insecticide resistance profile, and the physicochemical properties of their breeding sites in Sharada and Wailari of Kano State, Nigeria. Six breeding sites from the 2 study areas were sampled and their physicochemical parameters determined. Mosquito larvae were sampled from the sites and reared to adult. The emergent adults were morphologically and molecularly identified to species level. The World Health Organization (WHO) susceptibility assay was carried out on the adult mosquitoes using different classes of insecticides in WHO discriminating concentrations. kdr-mutation was detected by polymerase chain reaction (PCR)-based method using the permethrin (pyrethroid) resistant and susceptible adult mosquitoes. Most of the determined physicochemical parameters were significantly higher in the industrial area, Sharada. Morphologically, the mosquitoes from the 2 sites were identified as Anopheles gambiae and 100% of the randomly sampled population were found to be Anopheles coluzzii by PCR-based molecular technique. The WHO susceptible assay revealed a graded level of resistance to bendiocarb, dichlorodiphenyltrichloroethane (DDT), and permethrin with mortalities of 78.36%, 75.74%; 43.44%, 56.96%; and 37.50%, 37.50% in both Sharada and Wailari, respectively. Pre-exposure to piperonyl butoxide (PBO) resulted in a significant but minor recovery of susceptibility to permethrin. The kdr mutation frequency was higher in Sharada (45.71%) relative to Wailari (31.43%). Higher kdr mutation frequency was also observed in the resistant population (48.56%) relative to the susceptible (28.54%). The kdr mutation frequency was weakly associated with the resistance status (odds ratio [OR]: 5.9, χ 2 :3.58, P  = .058) and the breeding sites (OR: 3.46, χ 2 :2.90, P  = .088). In conclusion, the study revealed a highly pyrethroid-resistant A coluzzii population with low PBO recovery rate. Furthermore, the data suggested the involvement of kdr mutation, detoxification enzyme, and possibly abiotic factors of the breeding sites.